2000
DOI: 10.1007/bf02236858
|View full text |Cite
|
Sign up to set email alerts
|

Defining the role of laparoscopic-assisted sigmoid colectomy for diverticulitis

Abstract: Laparoscopic-assisted sigmoid colectomy for diverticulitis can be safely performed. Conversion appears to be associated with complicated diverticulitis (fistula or abscess), which may be better approached by laparotomy. Short-term follow-up indicates that recurrence is rare and suggests that laparoscopic-assisted sigmoid colectomy achieves adequate resection. Laparoscopic-assisted sigmoid colectomy offers benefits of decreased ileus and length of stay and may represent the procedure of choice for elective rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
63
1
5

Year Published

2003
2003
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(86 citation statements)
references
References 17 publications
14
63
1
5
Order By: Relevance
“…22,51,52 Conversion has traditionally been associated with higher morbidity, 6,7,53 but this has been challenged. 5,37 In a multi-center prospective study of laparoscopic management of diverticulitis, Scheidbach et al found that complication and conversion rates were initially higher in complicated disease but improved with surgeon experience. 54 In a recent comparative analysis between laparoscopic versus open anterior resection for recurrent and complicated diverticulitis, Lu et al demonstrated significantly shorter operating times, earlier return of bowel function, shorter hospital stay, and a low conversion rate (3%).…”
Section: Management Of Diverticular Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…22,51,52 Conversion has traditionally been associated with higher morbidity, 6,7,53 but this has been challenged. 5,37 In a multi-center prospective study of laparoscopic management of diverticulitis, Scheidbach et al found that complication and conversion rates were initially higher in complicated disease but improved with surgeon experience. 54 In a recent comparative analysis between laparoscopic versus open anterior resection for recurrent and complicated diverticulitis, Lu et al demonstrated significantly shorter operating times, earlier return of bowel function, shorter hospital stay, and a low conversion rate (3%).…”
Section: Management Of Diverticular Diseasementioning
confidence: 99%
“…5,37,68 However, many studies of laparoscopic resection for complicated diverticulitis have included colovesical fistulas and demonstrated acceptable results. 3,7,48,50,54,56,58,69 In their comparative study of laparoscopic management of recurrent uncomplicated disease versus complicated disease, Zapletal et al included 8 colovesical fistulas and reported no mortality, major complications, or conversions in these patients.…”
Section: Laparoscopic Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, another four patients (2%) underwent conversion to a hand-assisted technique. This rate still is lower than the 26% quoted by Vargas et al [2], although not as low the rate cited by Reissfelder et al [3]. In terms of Table 4, the papers by both Vargas et al [2] and Reissfelder et al [3] described the technique as laparoscopically assisted.…”
mentioning
confidence: 67%
“…This rate still is lower than the 26% quoted by Vargas et al [2], although not as low the rate cited by Reissfelder et al [3]. In terms of Table 4, the papers by both Vargas et al [2] and Reissfelder et al [3] described the technique as laparoscopically assisted. Do the authors believe their technique differs from the procedure described in these papers they have chosen to use for their comparisons?…”
mentioning
confidence: 67%